Inquiry of the truth, legislative rationality and legal process: about the rule of recognition in the colombian criminal process (2010)
The rule of recognition stated in the final subsection of the 29th article of the Colombian Constitution as a guarantee of the fundamental rights system, is reflected in the new regulation of the Criminal Procedure Statute (Ley 906 de 2004), in which it i